Good Corporate Governance In The Perspective Of Communication Ethics At Bum Desa Mandiri Sakti Grenggeng Kebumen - Umi Arifah; Muhammad Fajrul Hakim; Putri Rahmawati; Sidik Fajar Pratama (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
Research conducted on the Implementation of Good Corporate Governance in the Perspective of Communication Ethics at BUM Desa Mandiri Sakti Grenggeng, Karanganyar, Kebumen. The research objectives are as follows: 1) analyze the implementation of Good Corporate Governance at BUM Desa Mandiri Sakti Grenggeng; 2) analyze Good Corporate Governance from the perspective of communication ethics at BUM Desa Mandiri Sakti Grenggeng. This research uses qualitative research methods by collecting data through interviews, documentation, and observation. Research data analysis was carried out using Data Analysis Procedure by Application (DAPA), namely Atlas.ti as qualitative analysis with high visualization features. The research results show that BUM Desa Mandiri Sakti Grenggeng in its implementation uses the principles of accountability, responsibility, transparency, fairness, and independence. The communication ethics applied are communication ethics from a human perspective, a situational perspective, and a dialogic perspective.